UJI AKTIVITAS ANTI JAMUR SEDIAAN GEL EKSTRAK DAUN TURI PUTIH (Sesbania grandiflora L.) TERHADAP JAMUR Candida albicans - Sinta ardani; Supriyanto; Wahyu Purwanjani (Joseph: Journal of Science and Pharmacy, 2024)
Background: One of the plants that has anti-fungal potential is the white Turi Plant (Sesbania grandriflora) white turi leaf extract (Sesbania grandiflora) which is suspected to be able to inhibit the growth of Candida albicans, one of the fungi that cause candidiasis. Purpose: This study aims to determine the antifungal activity of Sesbania grandriflora white turi leaf extract gel against the fungus Candida albicans, determine the minimum inhibitory concentration (KHM) and determine the content of secondary metabolite compounds. Method: The leaves (Sesbania grandriflora) are extracted by maceration with a 70% ethanol solvent. The extracts obtained were subjected to phytochemical screening tests. The antifungal activity test of turi leaf extract gel was carried out by the well method against Candida albicans. The positive control used was the 2% dandruff gel while the negative control used was the gel preparation without the extract. Results: White turi leaf extract gel (Sesbania grandriflora) has antifungal activity against Candida albicans. Conclusion: Based on the results of the research on the Antifungal Activity Test of Sesbania glandriflora White Turi Leaf Extract Gel Preparation against Candida albicans Fungus, it can be concluded as follows: 1. Sesbania glandriflora (L.) white turquoise leaf extracthas the content of Saponins, flavonoids, and tannins  2.  Sesbania glandriflora (L.) white turquoise leaf extractgel preparation has the activity of inhibiting the fungusCandida albicans   The most effective formulation of Sesbania glandriflora (L.) white turi extract gel preparation against the growth of Candida albicans fungus is Formulation 3 with a concentration of 8% of 20.65 mm, included in the very strong group